1999
DOI: 10.1111/j.1745-4573.1999.tb00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Instrumental and Visual Color in a Raw, Fresh Beef and Chicken Model System

Abstract: A range of meat redness was created by mixing fresh, chilled ground chicken breast and ground beef in predetermined ratios. Samples were scored for visual redness under halogen (incandescent) and cool white fluorescent lighting. Instrumental color characteristics (L*, a*, b*, hue angle, chroma; illuminants A and F) and red color contributed by oxymyoglobin (percentage reflectance at 630 nm versus 580 nm) were determined. Correlation coefficients were determined between visual and instrumental evaluations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…Lower L* and slightly higher b* values in the control group indicated darker coloured breast meat compared to the vitamin E supplemented group. Colour differences on CIE-Lab coordinates can be discerned by the most normal observers, and consumers can detect one CIE-Lab unit change in colour coordinates (Zhu & Brewer, 1999). Although there were no statistically significant differences in the b* values of groups, colour development in the vitamin E supplemented group could be detected by the naked eye as light coloured breast meat, compared to other groups.…”
Section: Resultsmentioning
confidence: 83%
“…Lower L* and slightly higher b* values in the control group indicated darker coloured breast meat compared to the vitamin E supplemented group. Colour differences on CIE-Lab coordinates can be discerned by the most normal observers, and consumers can detect one CIE-Lab unit change in colour coordinates (Zhu & Brewer, 1999). Although there were no statistically significant differences in the b* values of groups, colour development in the vitamin E supplemented group could be detected by the naked eye as light coloured breast meat, compared to other groups.…”
Section: Resultsmentioning
confidence: 83%
“…The ME and MEZ treatments resulted in meat with a lower L*, hue, and chroma equating to a darker, redder colour of lower intensity, respectively, as compared to CON and ENZ (Table 1). Although visual colour scoring was not conducted in this study, the differences between the phosphate-containing samples (ME, MEZ) and those without phosphate treatment (CON, ENZ) were quite apparent upon visual examination, with the differences in instrumental colour values falling well within the limits for visual detection described by Zhu and Brewer (1999). Robbins et al (2002) also reported a darker colour in phosphate-injected beef rounds and suggested the colour effect was a result of an increased pH.…”
Section: Resultsmentioning
confidence: 73%
“…These results, together with the lack of difference in meat redness (a*) and saturation (C*) between treatments, confirm previous findings showing that, in lambs (Luciano et al, 2009), differences in meat colour between concentrate-and pasture-fed animals are not evident when animals are allowed to grow at comparable rates. Moreover, it is also evident that colour differences of one CIE-LAB coordinate can be discerned by most normal observers (Hunter and Harold, 1987) and consumers can detect one CIELAB unit change in colour coordinates (Zhu and Brewer, 1999). Thus colour development in two groups could be detected by eye.…”
Section: Resultsmentioning
confidence: 79%